Synthesis and colloidal characterization of folic acid-modified PEG-b-PCL Micelles for methotrexate delivery - Brandt, João Victor [UNESP]; Piazza, Rodolfo Debone [UNESP]; dos Santos, Caio Carvalho [UNESP]; Vega-Chacón, Jaime [UNESP]; Amantéa, Bruno Estevam [UNESP]; Pinto, Gabriel Cardoso [UNESP]; Magnani, Marina [UNESP]; Piva, Henrique Luís; Tedesco, Antonio Claudio; Primo, Fernando Lucas [UNESP]; Jafelicci, Miguel [UNESP]; Marques, Rodrigo Fernando Costa [UNESP] (Elsevier, 2019)
Hydrophobic drugs, such as methotrexate, are not easily delivered into the human body. Therefore, the use of amphiphilic nanoplatforms to the transport of these drugs through the bloodstream is a challenge. While the hydrophobic region interacts with the drug, the hydrophilic outer layer enhances its bioavailability and circulation time. Poly (ethylene glycol)-block-poly(ε-caprolactone) PEG-b-PCL micelles are biodegradable and biocompatible, allowing its use as a nanocarrier for drug delivery systems. The stealth property of PEG that composes the outer layer of nanoplatforms, makes the micelle unperceivable to phagocytic cells, increasing the circulation time in the human body. In addition, folic acid functionalization enables micelle selectively targeting to cancer cells, improving treatment efficiency and reducing side effects. In this work, PEG-b-PCL copolymer was synthesized by ring opening polymerization (ROP) of the ε-caprolactone with Poly(ethylene glycol) as a macroinitiator and tin(II) 2-ethyl hexanoate as a catalyst. Functionalization of such micelles with folic acid occurred through the modification of the PEG terminal group. The surface modification of the copolymer micelles resulted in higher critical micellar concentration (CMC), increasing approximately 100 times. The synthesis of the copolymers resulted in molecular weight around 3000 g mol −1 with low polydispersity. The polymer micelles have a hydrodynamic diameter in the range of 100–200 nm and the functionalized sample doesn't show aggregation in the considered pH range. High incorporation efficiency was obtained with a minimum percentage of 85%. The drug release profile and linearization from the Peppas model confirmed the interaction of methotrexate with the hydrophobic segment of the copolymer and its release mechanism by relaxation and/or degradation of the chains, making PEG-b-PCL micelles suitable candidates for hydrophobic drug delivery systems.
Keywords: Copolymer micelles; Methotrexate; PEG-b-PCL; Targeted drug delivery